KEDUDUKAN PEMIMPIN PEREMPUAN DALAM PERSPEKTIF HUKUM ISLAM - Widya Agesna (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2018)
Abstracts: Attempts to discuss women's leaders in Islam are the courage to enter a region full of the dangers of excessive generalization, excessive simplification, and restrictions that are almost inevitable from Western bias. The first problem is only one of the unresolved problems. Most of these factors are directly related to Islam itself, such as current and past legal reality, roles that are permitted and carried out as a result of Muslim images of women and religious ceremonies and diverse Islamic practices , where Muslim women have traditionally participated. Other supporting elements to provide a complete picture of women in Islam such as education, political rights, professional employment opportunities, and the like, have little to do with religion, but are still influenced by it. The issue of female leaders in Islam has often been discussed before, but until now the problem has not been eroded completely. This is inseparable from the factors that led to differences of opinion among the scholars, community leaders even in the community itself.Keywords: Leader, Woman, Islamic Law